2007
DOI: 10.1002/anie.200601551
|View full text |Cite
|
Sign up to set email alerts
|

The Woodward–Doering/Rabe–Kindler Total Synthesis of Quinine: Setting the Record Straight

Abstract: In 1918, Paul Rabe and Karl Kindler reported the three‐step conversion of d‐quinotoxine into quinine. In 1944 Robert B. Woodward and William von Eggers Doering reported the total synthesis of homomeroquinene and d‐quinotoxine from 7‐hydroxyisoquinoline. Based on the transformations by Rabe and Kindler, Woodward and Doering asserted the “Total Synthesis of Quinine” (the title of their 1944 and 1945 papers). In 2000 and 2001, Gilbert Stork concluded that the claim by Woodward and Doering is a “myth” because they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 69 publications
0
48
0
4
Order By: Relevance
“…Stork's message to Prelog written in the author's travelling autograph book ( Figure 9) inquired if Prelog, or anyone known to Prelog, had repeated the Rabe and Kindler conversion of quinotoxine to quinine. The historical research by Seeman in 2007 [35] and the experimental studies by Smith and Williams in 2008 [54] confirmed Figure 11A]. It shows the conversion of hinokitiol to substituted 1,3-azulene dicarboxylic acids.…”
Section: Collectables and Conversations: Nozoe And His Autograph Bookmentioning
confidence: 69%
See 1 more Smart Citation
“…Stork's message to Prelog written in the author's travelling autograph book ( Figure 9) inquired if Prelog, or anyone known to Prelog, had repeated the Rabe and Kindler conversion of quinotoxine to quinine. The historical research by Seeman in 2007 [35] and the experimental studies by Smith and Williams in 2008 [54] confirmed Figure 11A]. It shows the conversion of hinokitiol to substituted 1,3-azulene dicarboxylic acids.…”
Section: Collectables and Conversations: Nozoe And His Autograph Bookmentioning
confidence: 69%
“…Koji was particularly playful as he often is when relaxing at restaurants that serve sake. But Gilbert asked a very serious question, a question whose meaning and substance I would only discover nearly ten years later when I was studying [35] the validity of Stork's claim [36][37][38][39] that the Woodward-Doering total synthesis of quinine [40,41] was a "myth." (Woodward received the Nobel Prize in 1965.)…”
Section: Collectables and Conversations: Nozoe And His Autograph Bookmentioning
confidence: 99%
“…It was through the effort of the alkaloid chemists Königs, Skraup and Rabe that this problem was solved, over a period of 30 years from 1880 to 1910. The synthesis of quinine was finally formally achieved by the Woodward-Doering/Rabe-Kindler synthesis, a matter of utmost interesting and exciting controversy, recommended reading to every phytochemist (Seeman, 2007). Interestingly, the first stereoselective and unambiguous total synthesis of quinine was reported by Stork et al in 2001, 181 years after the discovery of this alkaloid.…”
Section: Isolation Crystallization Structural Determination Of Alkamentioning
confidence: 97%
“…Sometimes, my lectures are part of the institution’s mandated RCR training program. Other times, I speak about my own research in RCR (House and Seeman, 2010; Seeman and House, 2010a,b) and history and sociology of chemistry as they relate to RCR (for example, see Seeman, 2007). While there are many valuable resources available for use in RCR educational programs, including a number of excellent texts (Beach, 1996; Committee on Assessing Integrity in Research Environments, 2002; Panel on Scientific Responsibility and the Conduct of Research, 1992; Panel on Scientific Responsibility and the Conduct of Research, 1993; Lock and Wells, 1996; Macrina, 2014; Resnik, 1998; Seebauer and Barry, 2001; Shamoo and Resnik, 2015; Steneck, 2007), there is only one that specifically focused on the chemical community—the book The Ethical Chemist: Professionalism and Ethics in Science (Kovac, 2004).…”
mentioning
confidence: 99%